Community midwives' acceptability in their communities: A qualitative study from two provinces of Pakistan. (April 2017) - Ahmed, Jamil; Ur Rehman, Shafiq; Shahab, Muhammad
Abstract: Objectives: this study was aimed to understand in depth how the community midwives (CMWs) in Pakistan perceive are the important factors for their acceptability and community related barriers to their practice of maternal and child health care services. Design: qualitative study design using in-depth interviews (IDIs) and focus group discussions (FGDs). Setting: two districts in Khyber Pakhtunkhwa and Punjab provinces in Pakistan. Participants: we used qualitative study design and conducted 34 in depth interviews (IDIs) and 9 focus group discussions (FGDs) with 100 participants which included CMWs, lady health supervisors (LHSs) and managers in maternal neonatal and child health (MNCH) program of two provinces of Pakistan. Measurements: content analysis of the findings was performed manually and findings were arranged in relevant themes originating from the study. Findings: CMWs in our study experienced restrictions from their families, especially husbands and in-laws, to be independently available to attend to women during pregnancy and delivery. Communication between the communities and MNCH program was found to be weak therefore CMWs had to struggle to win the trust of and persuade pregnant women to use their services. Most CMWs attributed low utilization of their services to inherent taboos prevalent in the communities under which they relied more on unskilled traditional birth attendants (TBAs). Gender sensitivity and fears of insecurity in many conflict hit areas affected CMWs' mobility within their own communities which affected the access of rural women to skilled maternal and child care.